2010
DOI: 10.1007/s10151-010-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Perineal endometriosis: a case report and review of the literature

Abstract: Endometriosis is the presence of endometrial-like tissue outside the uterine cavity, which most commonly affects peritoneal surfaces, ovaries and uterine ligaments. Even it is quite rare, endometriosis may affect the vulva, vagina, rectovaginal septum or perineal region, generally secondary to obstetric or surgical trauma. In this case report, we present a patient with perineal endometriosis in an episiotomy scar. Diagnostic tools used included transvaginal and endorectal ultrasonography (USG), magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…There was no discolouration of the perineal skin, no local swelling or periodic leakage of dark coloured fluid. In some cases, bloody discharge oozing out from the scar has been reported,2 while a visible swelling was present in one case 3…”
Section: Discussionmentioning
confidence: 98%
“…There was no discolouration of the perineal skin, no local swelling or periodic leakage of dark coloured fluid. In some cases, bloody discharge oozing out from the scar has been reported,2 while a visible swelling was present in one case 3…”
Section: Discussionmentioning
confidence: 98%
“…However, incisional endometriosis as a result of recurrent caesarean sections laparoscopic surgery and also endometriosis on scars of trocar site have been reported. Also, literature reveals cases of episiotomy scar endometriosis developing on the scars of episiotomy incision performed during vaginal birth 2,3 . Laadi et al 4 have reported the case of deep endometriosis developing in the episiotomy scar.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is characterised by ectopic growth of endometrial tissue outside the uterine cavity5 and can cause dyspareunia when it affects the perineum and the vulva 2. Vulvar endometrial lesions usually occur after surgery6 or trauma7 but rarely spontaneously 8–10. The most common sites are episiotomy scars,6 11 Bartholin’s gland12 and more rarely labia majora2 or labia minora 13…”
Section: Introductionmentioning
confidence: 99%